Pemilihan Kepala/Wali Desa/Nagari Dengan Sistem E-Voting Di Kabupaten Agam Provinsi Sumatera Barat - Muhammad Irham; Miracle Soplanit (SASI, 2017)
Village head election must be continuously developed and adapted to the development of the community in the village. The Indonesian nation has stated clearly in the constitution of the 1945 Constitution of the Republic of Indonesia, the fourth paragraph which is the purpose of national and state life "...... protecting the whole Indonesian nation and the entire Indonesian blood sphere, and to promote general welfare, educating the life of the nation ". In 2017, 28 Nagari in Agam District will carry out the election of Head/Village Guard/Nagari. The elections will be held on 16, 19, 22, 25 and 29 July 2017, with a total of 128,000 voters, with an E-voting system. Through the e-voting system in the selection of Wali Nagari (Pilwana) it has made it easier for the villagers/nagari in choosing, and the potential for cheating is less than the paper voting system.